SERBIAN LABOUR LAW ACTUALITY AND NEW CHALLENGES - Obradović, Goran; Jašarević, Senad (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
THE TEXT GIVES A SHORT REVIEW AND GENESIS OF CONTEMPORARY SERBIAN LABOUR LAW. IT PROVIDES AN ANALYSIS OF THE ACTUALITY AND FUNCTIONALITY OF REGULATIONS WITHIN THE CONTEXT OF NEW NECESSITIES AND PRACTICE, AS WELL AS THEIR HARMONISATION WITH INTERNATIONAL STANDARDS. BASIC, SPECIFIC, SPECIAL AND AUXILIARY SOURCES OF SERBIAN LABOUR LAW ARE PRESENTED HEREIN. IT SPEAKS ABOUT WEAKNESSES AND INDIVIDUAL REGULATIONS AND THE NEW CIRCUMSTANCES IN THE WORLD IMPLICATING THE NEED TO MODERNISE SERBIAN LABOUR LEGISLATION.